APPLICATION OF COPYWRITING ELEMENTS IN SOCIAL MEDIA ADVERTISING DRINKING PRODUCTS NOW IN CREATING CONSUMER INTEREST - Jesslyn; Glorya Agustiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
ABSTRACT Advertising in social media is becoming a trend in business circles. One of the ways is to create creative content in social media in order to attract target market’s attention. Creative content is a form of content which is currently being developed on social media, especially Instagram. Diverse forms of creative contents can be found easily on Instagram accounts. One of them is creative contents uploaded by @xingfutang_indonesia on Instagram. Creative content creation cannot be separated from visual and copywriting elemts. In this case, copywriting becomes important in providing information to the target market. Referring to the concept, this study aims to determine the applied elements of copywriting which include headline and slogans, company taglines, and call to action used in creative contents on @xingfutang_indonesia account on Instagram. The research method used is a descriptive qualitative approach with content collection documentation and interviews as data collection techniques. The results of the research are beneficial for the scientific development of the field of communication, especially for the advertising industry in a practical way.